Semmering Base Tunnel – Ground characterisation for tendering and construction: Semmering‐Basistunnel – Gebirgsansprache in Ausschreibung und Bau. Issue 5 (2nd October 2017) - Wagner, Oliver Kai; Fasching, Alfred; Stadlmann, Thomas; Vanek, Robert
Abstract: Since the start of construction on contract SBT3.1 in May 2016, all three tunnel construction contracts for the Semmering Base Tunnel are now under construction. From the geological and geotechnical point of view, this represents the transition from the geotechnical prediction for the design for tendering to the documentation in the course of construction. The paper describes the considerations about the systematics of ground characterisation and the definition of ground types in the course of producing the ground prediction for the design for tendering. It also describes the requirements for the documentation of ground conditions encountered during the advance, the updating of the prediction for the daily specification of support measures and the comparison of prediction and actual conditions for contractual purposes.